2020
DOI: 10.29333/iji.2020.1312a
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Critical Thinking as a Mediator Variable in the Effect of Internal Locus of Control on Moral Disengagement

Abstract: The background of this research is the inconsistency of the results of previous research about the factors that influence moral disengagement. This study aims to determine the role of critical thinking as a mediator of the influence of internal locus of control on student moral disengagement. The population in this study were 1560 students of the State Islamic University (UIN) Sunan Gunung Djati Bandung who lived in boarding schools around the campus with a total of 300 respondents taken randomly. Data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…According to Kreitner &Kenicki (2009) andDeter, Trevino &Sweitzer (2008) internal locus of control was a factor that has a significant role in reducing moral disengagement behavior. Tahrir, Nurdin, & Damayanti (2020), and Aprilia & Solicha (2013) in their research also found that internal locur of control was a significant factor in reducing moral disengagement behavior . However, research by Ogunyemi (2013) that external locus of control could increase unethical behavior even though internal locus of control was also not a guarantee for individuals to behave ethically.…”
Section: Introductionmentioning
confidence: 79%
“…According to Kreitner &Kenicki (2009) andDeter, Trevino &Sweitzer (2008) internal locus of control was a factor that has a significant role in reducing moral disengagement behavior. Tahrir, Nurdin, & Damayanti (2020), and Aprilia & Solicha (2013) in their research also found that internal locur of control was a significant factor in reducing moral disengagement behavior . However, research by Ogunyemi (2013) that external locus of control could increase unethical behavior even though internal locus of control was also not a guarantee for individuals to behave ethically.…”
Section: Introductionmentioning
confidence: 79%
“…Second, business ethics practitioners should enhance the critical thinking abilities of employees and business students. Tahrir, Nurdin, and Damayanti (2020) found that critical thinking has a negative effect on moral disengagement. Those with critical thinking abilities identify, analyze, and evaluate information when they make decisions (Tahrir et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Tahrir, Nurdin, and Damayanti (2020) found that critical thinking has a negative effect on moral disengagement. Those with critical thinking abilities identify, analyze, and evaluate information when they make decisions (Tahrir et al, 2020). A systematic and critical thinking style makes it easy for individuals to avoid behaviors that violate laws and norms.…”
Section: Discussionmentioning
confidence: 99%
“…Another individual difference addressing the tendency to take responsibility is the internal locus of control (Rotter 1966). Consistently, there was a negative link between internal locus of control, which refers to people's evaluation of the consequences of their behavior by attributing them to their free will, and moral disengagement (Tahrir et al 2020). One possible reason for having a negative relationship might be that people with a high internal locus of control consider themselves more responsible for their behaviors, which in turn engage lower levels of selfregulation processes that help eliminate the distress caused by immoral acts.…”
Section: Individual Differences Related To Moral Disengagement Person...mentioning
confidence: 98%